Wilson’s scheme of the standard facial zones and microfacies and its perception in USSR and Russia - V. G. Kuznetsov (Известия высших учебных заведений: Геология и разведка)
The informative and in the whole interesting and useful book of James Wilson and, in particular, a principal scheme of the standard facial zones are analyzed. The book is shown to reflect only one and not most important carbonate sedimentation environments. The very environment is commonly used as an absolute etalon, reference to which does not demand any additional proves.